Social capital and HIV/AIDS in the United States: Knowledge, gaps, and future directions. (August 2018) - Ransome, Yusuf; Thurber, Katherine A.; Swen, Melody; Crawford, Natalie D.; German, Danielle; Dean, Lorraine T.
Abstract: Purpose: Social capital is a well-established predictor of several behavioral health outcomes. However, we know less about the relationship with prevention, transmission, and treatment of HIV/AIDS outcomes in the United States (US). Methods: In 2017, we conducted a scoping review of empirical studies investigating the relationships between social capital and HIV/AIDS in the US by searching PubMed, Embase, PsycINFO, Web of Science, and Sociological Abstracts with no restriction on publication date, for articles in English language. Sample search terms included: HIV infections OR HIV OR AIDS OR acquired immunodeficiency syndrome OR human immunodeficiency virus AND social capital OR social control, informal OR social participation OR social cohesion OR generalized trust OR social trust OR collective efficacy OR community mob* OR civic participation. Results: We identified 1581 unique manuscripts and reviewed 13 based on eligibility criteria. The earliest eligible study was published in 2003. More than half (n=7/13) focused on HIV or AIDS diagnosis, then prescribing ART and/or adherence (n=5/13), then linkage and or engagement in HIV care (n=4/13). Fifty eight percent (58%) documented a protective association between at least one social capital measure and an HIV/AIDS outcome. Seven studies used validated social capital scales, however there was substantial variation in conceptual/operational definitions and measures used. Most studies were based on samples from the Northeast. Three studies directly focused on or stratified analyses among subgroups or key populations. Studies were cross-sectional, so causal inference is unknown. Conclusion: Our review suggests that social capital may be an important determinant of HIV/AIDS prevention, transmission, and treatment outcomes. We recommend future research assess these associations using qualitative and mixed-methods approaches, longitudinally, examine differences across subgroups and geographic region, include a wider range of social capital constructs, and examine indicators beyond HIV diagnosis, as well as how mechanisms like stigma link social capital to HIV/AIDS. Highlights: Social capital and HIV/AIDS studies in the USA were evaluated. 54% of studies focused on HIV or AIDS diagnosis. 58% of studies found a protective association. Operational definition of social capital and measures varied across studies. Studies on the topic are increasing in the USA.